Doing Well in Life? Thank Your Big Sister (Center For Global Development)
Older siblings—particularly sisters—play a much larger role in caring for young children in many low- and middle-income country (LMIC) contexts, particularly in rural areas and among households engaged in subsistence agriculture and other forms of domestic production. In spite of this, the role that older sisters play in childrearing is often ignored in research and policy discussions of early childhood.